2002
DOI: 10.1063/1.1431707
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of secondary electron emission and plasma density enhancement for plasma exposed surfaces using an optically isolated Faraday cup

Abstract: We present secondary electron yield and plasma enhancement factor data for silicon surfaces exposed to Ar, He, N2, O2, H2, and BF3 plasmas, for incident ion energies from 0.5–10 keV. A fiber-optic isolated Faraday cup was used to directly measure the ion current Jion, allowing a direct measurement of the secondary electron yield. This method automatically accounted for the effect of pulse-induced plasma density enhancement due to the ionization of neutral gas by accelerated secondary electrons, which we observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 11 publications
3
18
0
Order By: Relevance
“…However, the above-mentioned analytical model and fluid model both neglect the secondary electron emission effect, and till now, few theoretical studies on the secondary electron emission in PSII have been carried out. Moreover, opinions on the effect of secondary electron emission still disagree with each other [59,60] . It is expected that the particle simulation method will accurately calculate the effect of secondary electron emission in PSII.…”
Section: Discussionmentioning
confidence: 97%
“…However, the above-mentioned analytical model and fluid model both neglect the secondary electron emission effect, and till now, few theoretical studies on the secondary electron emission in PSII have been carried out. Moreover, opinions on the effect of secondary electron emission still disagree with each other [59,60] . It is expected that the particle simulation method will accurately calculate the effect of secondary electron emission in PSII.…”
Section: Discussionmentioning
confidence: 97%
“…The values of measured by En and Cheung were comparable with those reported by Szapiro et al, while Shamim and coworkers found values of that were about twice those of Szapiro. Qin et al [16] found that these indirect methods ignore the phenomenon of plasma density enhancement during the high voltage pulse, which in turn increases the secondary yield, and developed a direct method based on a Faraday dosimetry technique for measuring the incident ion flux that automatically incorporates the effect of plasma density enhancement. Qin et al obtained secondary yields with values lower than those obtained by previous PIII methods but still higher than the standard methods.…”
Section: Introductionmentioning
confidence: 99%
“…For the pulsed continuous plasma systems used in the PIII process, people can only measure the quiescent plasma parameters without the pulses, 1,6,7 although the impact of the high-voltage pulses on the plasma densities has been qualitatively or semiquantitatively observed 8 and quantitatively measured. 4 Qin, et al used an in situ Faraday cup dosimetry technique to measure the plasma density enhancement factor e.f. ϭ J ion ͑on͒ / J ion ͑off͒ so that the averaged plasma density during the high voltage pulse can be obtained indirectly. 4 In this letter, a time-delayed and time-resolved Langmuir probe measurement was used to measure the evolution of the plasma densities versus time of a dc pulsed, noncontinuous plasma.…”
mentioning
confidence: 99%
“…4 Qin, et al used an in situ Faraday cup dosimetry technique to measure the plasma density enhancement factor e.f. ϭ J ion ͑on͒ / J ion ͑off͒ so that the averaged plasma density during the high voltage pulse can be obtained indirectly. 4 In this letter, a time-delayed and time-resolved Langmuir probe measurement was used to measure the evolution of the plasma densities versus time of a dc pulsed, noncontinuous plasma.…”
mentioning
confidence: 99%